DESAIN MEDIA DAN BAHAN AJAR PAI BERBASIS APLLIKASI PADLET - Aldi Akbar Wibowo, - (2023)
Learning media is an important component in learning because it's the main capital for creating conducive, fun, and not boring learning. So, an Islamic Religion teacher must be able to develop learning media in accordance with curriculum and the times growth. However, there are still many teachers who aren't competent and Culture Shock with technology-based learning media. Using ICT is very important for teachers to face the current development of the industrial revolution 4.0 and the era of digitalization. Thus, teachers must also master technology coupled with digital literacy skills as capital to develop learning media that is attractive to students so that the class atmosphere is happier and more enjoyable. Furthermore, teachers can add the attractiveness of learning and develop competence and professionalism as Islamic Religion teachers. Therefore, this research was conducted to dissect how the design of Islamic Religion media and teaching materials based on IoT technology, especially using Padlet application. This research was conducted at SMA Negeri 1 Sumedang using the exploratory sequential design hypothesis model method with interview, observation, and documentation study techniques. As a guarantor of data authenticity, researchers refer to four things, namely credibility, transferability, dependability, and conformability. The results of this study: First, Padlet is suitable as an innovation for the development of Islamic Religion media and teaching materials because it can be adapted to curriculum, principles of media and teaching materials development. Second, Padlet received a positive response from students and Islamic Religion teachers. Third, Padlet is able to increase Professionalism, Competence, and Digital Literacy for Islamic Education teachers.